KAJIAN FAKTOR-FAKTOR PENENTU KUNJUNGAN LANSIA KE POSYANDU LOURDES, KELURAHAN OETETE WILAYAH KERJA PUSKESMAS OEBOBO - Roberto Istefanus Sesfao; Sigit Purnama; Helga J N Ndun (Jurnal Pangan Gizi dan Kesehatan, 2022)
The elderly are a group of people who are at an age at risk of experiencing physical and psychological disorders, thus requiring continuous health monitoring. One of the efforts to monitor the health of the elderly can be done through the Posyandu for the elderly. This study aims to describe the behavior of elderly visits, the distance to the posyandu for the elderly, family support and perceptions of the elderly's needs for the elderly posyandu. This type of research is a descriptive research with case study research method. The research location is the Lourdes Elderly Posyandu, Oebobo Village in the month of March-April 2022. The population of this study is all elderly registered at the Lourdes Posyandu, Oetete Village, totaling 50 elderly. The sample in this study was the elderly who were recorded as visiting the Lourdes Posyandu, Oetete Village in the last month of the implementation of the Elderly Posyandu from the time the research was carried out. The sampling technique in this study was accidental sampling, namely the technique of determining the sample based on chance, namely the respondents who coincidentally/incidentally met the researcher when the research was carried out, namely as many as 14 elderly people.